Clinical significance of the two-base insertion mutation in the TP53 gene in canine histiocytic sarcoma. (June 2019) - Asada, Hajime; Tomiyasu, Hirotaka; Okada, Kazuki; Chambers, James K.; Goto-Koshino, Yuko; Uchida, Kazuyuki; Kagawa, Yumiko; Ohno, Koichi; Tsujimoto, Hajime
Abstract: Canine histiocytic sarcoma (HS) is an aggressive tumor type originating from dendritic cells or macrophages. We previously reported high incidence of the two-base (AT) insertion mutation (insAT) in the tumor protein p53 ( TP53 ) gene in dogs with HS, and the aim of this study was to investigate the clinical significance of insAT in canine HS. The present study established a sensitive digital PCR-based assay for detecting insAT and examined its associations with clinical variables and survival time. The mutation was detected in 26 of 64 dogs (41%), and the mean mutant allele frequency was 1.9% (range, 0.014–35%), indicating that not all tumor cells harbor insAT. The incidence of insAT was significantly higher in dogs with metastatic lesions than in those without metastatic lesions. However, the existence of insAT was not associated with survival time or response to chemotherapy with lomustine or nimustine. This study suggested that HS cells might acquire insAT in the TP53 gene during development of metastasis, but insAT was not a prognostic factor in canine HS. Further studies are needed to investigate the contribution of insAT to the development of metastatic lesions of canine HS. Highlights: Mutations of the TP53 gene are often observed in canine histiocytic sarcoma. Common 2-base insertion mutation in the TP53 gene was associated with metastasis. This mutation in the TP53 gene was not associated with response to chemotherapy. This mutation in the TP53 gene was not a prognostic factor.